Regional integrated interpretation of the hydrocarbon prospectivity of the Nile Delta, Offshore Egypt - Hanafy, S.; Nimmagadda, Shastri; Mahmoud, S.; Mabrouk, W.; Farhood, K. (Springer, 2016)
© 2016, Saudi Society for Geosciences. Interpretation of 2500 km of newly processed 2D seismic and regional potential field data has led to the identification of two new Miocene–Oligocene sedimentary basins in the northern part of offshore Egypt. The western part of the basin is deeper and has thick sedimentary cover. The upper part of the Miocene section is tested in its southern part through two wells, where the eastern subbasin is still virgin and is located at the intersection between Temsah basins and southeastern end of the Levantine basin. The main sedimentary unit of the basin is the Miocene–Oligocene sedimentary section, which was proven by the exploration and production activities in Nile Delta to be one of the hydrocarbon-generating facies. This fact is supported by 1D basin analysis using the average parameter values, which shows a hydrocarbon window, extending from lower Miocene to upper Miocene. The basin dimensions are more than 2000 km2 area and more than 4000 m of thickness, with variable petroleum system parameters’ potentialities, starting from Tortonian–Serravallian to lower Oligocene section.